A política do cartão nacional de saúde sob a ótica dos usuários do SUS na região metropolitana de João Pessoa e Recife - Martins, Márcia Maria de Medeiros Travassos Saeger (2009)
Throughout its history, Brazil has been finding many difficulties in education, economy, security, politics and health. The poor sections of the population - which is a large majority of people in relation to the ones who have more conditions - depend on governmental actions to make use of education and good health care among other services. One of the ways used to find solution to improve public health care services in the country was to create the Unique Health Care System (Sistema Único de Saúde - SUS), which aims at altering inequality in health care assistance to the population, imposing public attendance to any citizen, being prohibited the charge of money under any circumstances. With the increase in advances in technology around the world, public administration has been inserting in its practice devices that information technology (IT) disposes. In the public health care field, besides the Information systems in health, the national health card -or SUS card - represents one of the biggest projects developed by the government, using information systems that integrate all governmental spheres, providing a bigger financial control of the Ministry of health. The SUS card makes the access of registered patients to the SUS services possible, but at the same time it should not obstacle the access of the ones who do not have the card yet. According to the Health Ministry, one of the objectives of SUS card is to raise quality and efficiency in access to public health services. Ahead of the investments carried through in technology, an increase productivity is waited, that reflects in benefits to the population. This research aims at bringing to the reader the way as the users of SUS perceives the politics of SUS Card. Therefore public hospital patients in the metropolitans regions of João Pessoa and Recife were interviewed and the evaluation results proceeded from content analysis, proposed by Gläser and Laudel, with variables and dimensions established from the SERVQUAL model, scientifically validated. It was verified, to the end of the analysis, that the users of SUS do not feel themselves benefited with the implantation of SUS Card, what it makes possible the conclusion of that the high expenses of the Government with SUS Card had not been reverted in benefits to the population.